Fact and fantasy about leadership - Popper, Micha (Cheltenham Edward Elgar, 2012)
Why are we attracted to leaders? Does this attraction have universal origins or is it culture-bound? Why and how are certain concepts and myths regarding leaders generated? Analyzing the psychology of followers, this unique book explores these important questions. Micha Popper expertly offers new and surprising insights regarding the leadership phenomenon whilst providing relevant examples.
Includes bibliographical references and index.
Keywords: Leadership